Experimental study on active structural acoustic control of rotating machinery using rotating piezo-based inertial actuators. (21st July 2015) - Zhao, G.; Alujević, N.; Depraetere, B.; Pinte, G.; Swevers, J.; Sas, P.
Abstract: In this paper, two Piezo-Based Rotating Inertial Actuators (PBRIAs) are considered for the suppression of the structure-borne noise radiated from rotating machinery. As add-on devices, they can be directly mounted on a rotational shaft, in order to intervene as early as possible in the transfer path between disturbance and the noise radiating surfaces. A MIMO (Multi-Input−Multi-Output) form of the FxLMS control algorithm is employed to generate the appropriate actuation signals, relying on a linear interpolation scheme to approximate time varying secondary plants. The proposed active vibration control approach is tested on an experimental test bed comprising a rotating shaft mounted in a frame to which a noise-radiating plate is attached. The disturbance force is introduced by an electro-dynamic shaker. The experimental results show that when the shaft spins below 180 rpm, more than a 7 dB reduction can be achieved in terms of plate vibrations, along with a reduction in the same order of magnitude in terms of noise radiation.